(untitled) (Scientific journal of the Fergana State University, 2025)
The article analyzes that neighborhoods in New Uzbekistan have a very long history, are a unique social structure that has been developed over the centuries in organizing the daily social life and livelihood of the Uzbek people, uniting and organizing the population regardless of their nationality, social origin, and religious beliefs, and is an effective tool for attracting people to active social life. It is precisely these neighborhood bodies that are responsible for the development of the relevant territory and the state of the work being done.